Long Non-coding RNA MAFG-AS1 Promotes Cell Proliferation, Migration, and EMT by miR-3196/STRN4 in Drug-Resistant Cells of Liver Cancer - Chen, Tianming; Huang, Bin; Pan, Yaozhen (Frontiers in Cell and Developmental Biology, 2021)
Long non-coding RNAs (lncRNAs) have been shown to participate in the development and progression of several different types of cancer. Past studies indicated that lncRNA MAFG-antisense 1 (AS1) promotes colorectal cancer. However, the role of MAFG-AS1 in hepatocellular carcinoma (HCC) remains unclear. The aim of the present study is to examine the effect of lncRNA MAFG-AS1 on drug resistance HCC. The results indicated that MAFG-AS1 is upregulated in drug-resistant cells. Further, MAFG-AS1 promotes growth and migration of HCC by upregulating STRN4 through absorbing miR-3196. Thus, LncRNA MAFA-AS1 may become a novel target to treat HCC patients.